Menembus Formalisme Organisasi: Mencermati Tradisi Volunterisme di PM Gontor 7 Putera Sulawesi Tenggara - Badarwan Badarwan; Syahrul Syahrul (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
This study aims to examine the tradition of volunteerism in Pondok Modern Gontor 7 Putera Southeast Sulawesi, which includes basic values developed in building the tradition of volunteerism and Pondok Modern Gontor 7 Putera efforts to encourage his citizens to produce the best performance. The research method used is a qualitative descriptive method. Data collection is done through interviews, observations, and documentation. Data were analyzed through the stages of reduction, display, and verification. Data validity is tested through member check, triangulation, extended observation, and increased perseverance. The results of this study indicate that voluntary behavior is an application of the values of the five souls which are sincerity, simplicity, independence, ukhuwah Islamiyah, freedom, which is the basis in carrying out self-service and self-giving attitude. In improving performance, leaders motivate implementing the concept of five souls as the main reference in carrying out their duties and responsibilities, including in the application of management functions.